Interaction effects of FTO rs9939609 polymorphism and lifestyle factors on obesity indices in early adolescence. Issue 4 (July 2019) - Jiang, Yanrrui; Mei, Hao; Lin, Qingmin; Wang, Jian; Liu, Shijian; Wang, Guanghai; Jiang, Fan
Abstract: Background: The rs9939609 SNP in fat mass and obesity-associated ( FTO ) gene influence obesity, whose effects might be mediated by lifestyle factors. However, evidence was lacked in early adolescents. This study aimed to investigate the interactions effects of FTO rs9939609 and lifestyle factors on obesity indices in early adolescence. Methods: The study included 1149 children aged 10–12 years. Their body mass index (BMI) and body fat percentage (BF%) were measured, and lifestyle factors were surveyed through questionnaires. The rs9939609 SNP in the FTO gene was genotyped. Results: Significant associations were found between FTO rs9939609 and obesity indices after adjusting for confounding factors. An interaction effect between rs9939609 and soft drinks was observed with p  = 0.019 for BMI after adjustment for confounding factors. The children carrying risk allele A had a significantly higher mean BMI (mean=19.67kg/m 2 ) than those carrying only the wild allele T (mean = 17.987 kg/m 2 ) when they reported a higher intake of soft drinks (≥3 times/week), but the association was not observed among children with a lower intake of soft drinks. No significant interactions were established between appetite, weekday TV viewing, sleep, exclusive breast feeding in the first four months and FTO rs9939609 on BMI or BF%. Bioinformatics revealed that rs9939609 and its linkage disequilibrium (LD) SNPs are potentially implicated in the regulation of gene expression in blood, pancreatic and brain tissue cells. Conclusion: FTO rs9939609 had an obvious and independent effect on obesity-related indices in early adolescents. Soft drinks may exert a modifying effect on the relationship between FTO rs9939609 and BMI.